Enabling High Efficiency of Hydrocarbon‐Solvent Processed Organic Solar Cells through Balanced Charge Generation and Non‐Radiative Loss. Issue 41 (3rd October 2021) - Fan, Baobing; Lin, Francis; Oh, Jiyeon; Fu, Huiting; Gao, Wei; Fan, Qunping; Zhu, Zonglong; Li, Wen Jung; Li, Ning; Ying, Lei; Huang, Fei; Yang, Changduk; et al.
Abstract: Using non‐halogenated solvents to process organic solar cells is preferable because they are less harmful to human health. However, it is challenging to mitigate the delicate trade‐offs between solubility and pre‐aggregation of organic semiconductors to maintain similar high device efficiencies as those processed by chlorinated solvents. The need for rigorous control of the kinetics between processing temperature and delay time inevitably complicates device processing for achieving reproducible performance. Herein, the authors develop a facile method to achieve proper solubility and pre‐aggregation in non‐halogenated solvents by selecting suitable donor/acceptor materials and subtle tuning of solvent compositions. This results in films with a high degree of ordering and suitably sized phase separation. Solar cells derived from this process can achieve a high power conversion efficiency up to 18%, which is the highest value reported for non‐halogenated solvent processed devices. This impressive result is achieved through synergistically reduced non‐radiative loss and enhanced charge generation. Abstract : A facile strategy to achieve both proper solubility and pre‐aggregation in non‐halogenated solvents by selecting suitable donor/acceptor materials and subtle tuning of solvent compositions was developed. The derived solar cells achieve a high efficiency up to 18%, representing the highest value reported for non‐halogenated solvent processed devices.